Study of Retinopathy of Prematurity in Neonates With Unstable Clinical Course - Sharma, Mansi; Agrawal, Manish; Gupta, Vandana; Shukla, Prachi; Kumari, Kalpana (Journal of Neonatal Surgery, 2025)
Background: Retinopathy of Prematurity (ROP) is a major contributor to blindness in children, especially affecting infants born prematurely. Timely identification and treatment are essential to avert permanent vision impairment. Although neonatal care has improved, ROP continues to pose a worldwide health challenge, highlighting the need for screening and awareness of risk factors. Aim & Objectives: The objective of this study is to identify the risk factors and clinical characteristics of ROP in preterm infants at a tertiary care facility. Specific objectives include assessing the severity of ROP and its progression through follow-up evaluations. Material and Methods: This prospective, hospital-based research was carried out over a period of 18 months and involved 100 preterm infants, each with a gestational age of less than 37 weeks and a birth weight under 2 kg. Ophthalmic examinations were performed using binocular indirect ophthalmoscopy, and data were analyzed statistically to assess associations with risk factors. Results: Most infants were examined between 2 to 6 weeks of age, predominantly low birth weights, between 1 and 1.5 kg, born between 32 and 36 weeks gestation with risk factors such as respiratory distress and sepsis. At initial screening, 85% showed normal retinas, while 10% had Stage 1 ROP, 4% had Stage 2-3, and 1% had Stage 3+ with retinal detachment. After four weeks, 93% had normal retina, with no infants at Stage 1; two infants progressed to Stage 2. Statistical analysis showed no significant associations between most risk factors and severity. Conclusion: Early screening is vital in managing ROP, especially in high-risk preterm infants. The multifactorial nature of ROP underscores the need for vigilant monitoring and further research to optimize prevention and treatment strategies